Characteristics of Soda Pulp from Distilled Vetiver Root - Firda A Syamani; Subyakto Subyakto; Sukardi Sukardi; Ani Suryani (Masyarakat Peneliti Kayu Indonesia, 2014)
Cellulose was commonly extracted from wood and other lignocellulosic materials such as leaf, straw, bast, or grass. There is no report found on extraction of cellulose from root plant yet. Industrially, the root of vetiver is distilled to obtain its essential oil. In this study, the distilled vetiver root was soda pulped and the resulted pulp was characterized by the use of X-ray diffraction and FT-IR spectroscopic methods. Response surface methodology with central composite design was used to investigate the influence of delignification on the chemical properties of pulp. Soda pulping was carried out at 160 – 180 oC for 1 – 3 hrs with 20 – 40% of alkali charge. Severe process conditions were required to achieve a significant degree of delignification. Pulping at 180 oC for 3 hours with alkali charge of 40% decreased the lignin content of pulp from 39.53% to 4.47%.Keywords: FT-IR analysis, soda pulping, vetiver root, X-ray diffraction